KUALITAS PELAYANAN PENDIDIKAN MENENGAH DI SMP NEGERI 2 TALIABU UTARA KABUPATEN PULAU TALIABU (JURNAL ADMINISTRASI PUBLIK, 2020)
Service is to help to provide everything that others need including buyers. Service can be given toothers as a help that others themselves need. Which with that help can help others themselves. Whichwith that help can help others to be able to solve the problem. Professional public service means tocharacterize the accountability and responsiveness of the service provider. In order to achieve publicservice, it is necessary to understand the principles of good public service namely, simplicity, clarity,certainty, time, accuracy and comfort. The above principles of public service must be adapted to thedevelopment and needs of the community in realizing excellent public services in accordance with thedemands and expectations of the community.The implementation of public services is, the state's efforts to meet the basic needs, and civil rights ofevery citizen for the goods, services, and administrative services provided by public service providers.Key words: quality, of public, service.